Urinary biomarkers for the non-invasive diagnosis of endometriosis - Liu, Emily; Nisenblat, Vicki; Farquhar, Cindy; Fraser, Ian; Bossuyt, Patrick M M; Johnson, Neil; Hull, M Louise (Cochrane database of systematic reviews, 2015)
About 10% of reproductive-aged women suffer from endometriosis which is a costly chronic disease that causes pelvic pain and subfertility. Laparoscopy is the 'gold standard' diagnostic test for endometriosis, but it is expensive and carries surgical risks. Currently, there are no simple non-invasive or minimally-invasive tests available in clinical practice that accurately diagnoses endometriosis. 1. To provide summary estimates of the diagnostic accuracy of urinary biomarkers for the diagnosis of pelvic endometriosis compared to surgical diagnosis as a reference standard.2. To assess the diagnostic utility of biomarkers that could differentiate ovarian endometrioma from other ovarian masses.Urinary biomarkers were evaluated as replacement tests for surgical diagnosis and as triage tests to inform decisions to undertake surgery for endometriosis. The searches were not restricted to particular study design, language or publication dates. We searched the following databases to 20 April - 31 July 2015: CENTRAL, MEDLINE, EMBASE, CINAHL, PsycINFO, Web of Science, LILACS, OAIster, TRIP and ClinicalTrials.gov (trial register). MEDION, DARE, and PubMed were also searched to identify reviews and guidelines as reference sources of potentially relevant studies. Recently published papers not yet indexed in the major databases were also sought. The search strategy incorporated words in the title, abstract, text words across the record and the medical subject headings (MeSH) and was modified for each database. Published peer-reviewed, randomised controlled or cross-sectional studies of any size were considered, which included prospectively collected samples from any population of reproductive-aged women suspected of having one or more of the following target conditions: ovarian, peritoneal or deep infiltrating endometriosis (DIE). We included studies comparing the diagnostic test accuracy of one or more urinary biomarkers with surgical visualisation of endometriotic lesions. Two authors independently collected and performed a quality assessment of the data from each study. For each diagnostic test, the data were classified as positive or negative for the surgical detection of endometriosis and sensitivity and specificity estimates were calculated. If two or more tests were evaluated in the same cohort, each was considered as a separate data set. The bivariate model was used to obtain pooled estimates of sensitivity and specificity whenever sufficient data sets were available. The predetermined criteria for a clinically useful urine test to replace diagnostic surgery was one with a sensitivity of 94% and a specificity of 79% to detect endometriosis. The criteria for triage tests were set at sensitivity of equal or greater than 95% and specificity of equal or greater than 50%, which in case of negative result rules out the diagnosis (SnOUT test) or sensitivity of equal or greater than 50% with specificity of equal or greater than 95%, which in case of positive result rules the diagnosis in (SpIN test). We included eight studies involving 646 participants, most of which were of poor methodological quality. The urinary biomarkers were evaluated either in a specific phase of menstrual cycle or irrespective of the cycle phase. Five studies evaluated the diagnostic performance of four urinary biomarkers for endometriosis, including three biomarkers distinguishing women with and without endometriosis (enolase 1 (NNE); vitamin D binding protein (VDBP); and urinary peptide profiling); and one biomarker (cytokeratin 19 (CK 19)) showing no significant difference between the two groups. All of these biomarkers were assessed in small individual studies and could not be statistically evaluated in a meaningful way. None of the biomarkers met the criteria for a replacement test or a triage test. Three studies evaluated three biomarkers that did not differentiate women with endometriosis from disease-free controls. There was insufficient evidence to recommend any urinary biomarker for use as a replacement or triage test in clinical practice for the diagnosis of endometriosis. Several urinary biomarkers may have diagnostic potential, but require further evaluation before being introduced into routine clinical practice. Laparoscopy remains the gold standard for the diagnosis of endometriosis, and diagnosis of endometriosis using urinary biomarkers should only be undertaken in a research setting.